2022
DOI: 10.1111/ffe.13800
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of machine learning and stress concentration factors‐based fatigue failure prediction in small‐scale butt‐welded joints

Abstract: Fatigue behavior of welded joints is significantly influenced by numerous factors, for example, local weld geometry. A representative quantity for the influence of the notch effect created by the local weld geometry is the stress concentration factor (SCF). Thus, SCFs are often used to estimate fatigue failure locations and fatigue strength; however, this simplifies the mutual effect of other influencing factors. Consequently, fatigue strength estimates for welded joints may deviate from experimental results. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…A method is proposed and tested in this study for the probabilistic fatigue assessment of welded joints based on their individual geometrical parameters using a combination of methods from previous studies. 17,20,27,28 The geometrical parameters were evaluated from 3D surface scans of 26 test series from previous studies [30][31][32][33][34][35][36] of welded joints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A method is proposed and tested in this study for the probabilistic fatigue assessment of welded joints based on their individual geometrical parameters using a combination of methods from previous studies. 17,20,27,28 The geometrical parameters were evaluated from 3D surface scans of 26 test series from previous studies [30][31][32][33][34][35][36] of welded joints.…”
Section: Discussionmentioning
confidence: 99%
“…The geometrical parameters and fatigue test results taken from previous studies [30][31][32][33][34][35][36] and other unpublished investigations are summarized in Table 1. These data contain 390 single fatigue tests with four different types of welded joints: single V-butt joints, double V-butt joints, cruciform joints, and T-joints.…”
Section: Materials and Specimensmentioning
confidence: 99%
“…Since all of them are based on experimental or analytical data, they are not presented here, but some of them are referenced here for the benefit of readers. [136][137][138][139][140][141][142] In addition, many other recent papers presented also this important topic, some of them described briefly in the following text.…”
Section: Literature Overviewmentioning
confidence: 99%
“…A reinforcement ML method was developed to evaluate the effect of microstructural heterogeneity on the VHCF fatigue strength 13 . The comparison between the traditional stress concentration factor methods and ML prediction methods indicated that ML exhibits superior predictive performance 14 . The previous findings indicate that the application of ML method in the VHCF life prediction of high‐strength steel is feasible.…”
Section: Introductionmentioning
confidence: 99%